2008
DOI: 10.1590/s0104-42302008000500012
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculose pulmonar: associação entre extensão de lesão pulmonar residual e alteração da função pulmonar

Abstract: Rev Assoc Med Bras 2008; 54(5): 406-10 406 RESUMO OBJETIVO. Descrever as alterações nas variáveis da espirometria e seus distúrbios; estudar a existência de associação entre a extensão da lesão pulmonar residual ao final do tratamento da tuberculose e a alteração da função pulmonar aferida pela espirometria. MÉTODOS. Estudou-se uma série de 96 pacientes com diagnóstico de tuberculose pulmonar, atendidos em três unidades de saúde de Região Metropolitana do Recife, durante o período de janeiro de 2003 a novembro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
0
8
0
14
Order By: Relevance
“…These data suggest that healthy people had highly homogenous bacterial flora, while TB patients had a significantly altered bacterial community and a disappearance of any similarity. We interpreted the lack of homology as follows: from classical knowledge of TB pathology, Mycobacteria invasion is an important factor in injuring the mucosal barrier in the LRT, facilitating the colonisation of bacteria from the URT or foreign environments [ 24 ]. Our colleagues Cui et al have found that many rare, unique bacteria exist in the microbiota of sputum from TB patients compared with that of healthy individuals, indicating its important role in creating the diversity in TB microbiota [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that healthy people had highly homogenous bacterial flora, while TB patients had a significantly altered bacterial community and a disappearance of any similarity. We interpreted the lack of homology as follows: from classical knowledge of TB pathology, Mycobacteria invasion is an important factor in injuring the mucosal barrier in the LRT, facilitating the colonisation of bacteria from the URT or foreign environments [ 24 ]. Our colleagues Cui et al have found that many rare, unique bacteria exist in the microbiota of sputum from TB patients compared with that of healthy individuals, indicating its important role in creating the diversity in TB microbiota [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Case 3 shows a concomitant infection by M. hodleri , with very exuberant lung lesions. All patients described abandoned treatment, and had cavitary and fibro residual lesions and treatment failure, and showed no HIV coinfection, which is an association commonly described in the literature [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chest radiography predicts tuberculosis prognosis by evaluating pulmonary lesions [ 7 ], and it is still the most used imaging method [ 8 ]. Cavitary lesions and residual fibrosis found related to multidrug resistance corroborate the literature [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“… 11 However, OLD was observed in 33% of the patients evaluated by Di Naso et al 13 and in 49% of those evaluated by Nihues et al 14 At another center, RLD was the most prevalent (in 41%). 15 …”
Section: Introductionmentioning
confidence: 99%